Factors Influencing Customer Satisfaction: A Case Study of the E-Commerce Sector in Malaysia - Haslindar Ibrahim; Rudresh Pandey; Nurul Afiqah binti Yusoff; Nurul Anis Ezaty binti Hashim; Nurul Atirah binti Yunus; Nurul Aziera binti Katan; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
In the fast-paced digital era, e-commerce in Malaysia has experienced remarkable growth over the last decades. This surge is reflected in consumer behavior that has shifted from physical to online methods. Shopee, one of the e-commerce businesses in Malaysia. Assessing customer satisfaction in e-commerce is crucial as it helps Shopee enhance its competitive advantage. Therefore, this study aims to provide an analysis of the factors influencing customer satisfaction using Shopee for online purchase in Malaysia. Five main factors were identified in this study: perceived convenience, product quality, price perception, delivery service, website usability. An online survey questionnaire created using Google Form and distributed to 125 targeted Shopee users in Malaysia. SPSS used to analyze the data to examine the hypothesis or determine the significance of each factor in relation to customer satisfaction. Our findings underline that perceived convenience, product quality, price perception, delivery service, and website usability positively affect customer satisfaction. Product quality showed the highest influence compared to other factors. This study gives valuable information for Shopee to further improve its customer satisfaction